Midwifery Care through Complementary Postpartum Flipbook Learning Media Innovation with A Contextual Approach - Mutmainnah Mutmainnah; Musni Musni (Indonesian Journal of Global Health Research, 2024)
Midwifery education is the beginning of the birth of professional midwives. Midwifery education is the starting point and main point that will influence the level of quality of midwives and midwifery services in Indonesia. So lecturers need to think and design teaching materials that suit the interests of the current generation. The development of Flipbook teaching materials is equipped with various multimedia features with contextual methods so that students remain guided and interested in learning even though they are at home. Objective: The sample in this study was 31 level II midwifery students. Method: The study used type of R & D (Research and Development) research with the Borg & Gell development stages, development research with the initial stage of conducting a Focus Group Discussion (FGD) collecting information or data from sources appropriate to their field. To produce website-based products (Flipbooks). Continuing with black-box testing and testing the feasibility of the product using small samples using Quasi Experimental research (Pre-post-test design). Results: The Flipbook feasibility data analysis technique uses the Likert scale that is rated by the validator and Wilcoxon scales for field testing of the products produced. The research results show that the value (p=0.000<0.05) used Wilcoxon test. Conclusions: Conclusion which means that ASKEB Complementary Postpartum learning media innovation has a significant influence on increasing student knowledge.